2017
DOI: 10.3390/molecules22040489
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile of Skimmianine in Rats Determined by Ultra-Performance Liquid Chromatography Coupled with Quadrupole Time-of-Flight Tandem Mass Spectrometry

Abstract: Skimmianine is a furoquinoline alkaloid present mainly in the Rutaceae family. It has been reported to have analgesic, antispastic, sedative, anti-inflammatory, and other pharmacologic activities. Despite its critical pharmacological function, its metabolite profiling is still unclear. In this study, the in vivo metabolite profiling of skimmianine in rats was investigated using ultra-performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (UPLC/Q-TOF-MS). The metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
8
19
0
Order By: Relevance
“…The NMR data for compound 6 were assigned for the rst time according to its 2D-NMR data. From the 1 H-NMR data in Table 3 data, compound 16 is consistent with 4-hydroxy-7,8-dimethoxy-furoquinoline, which has been previously reported in the literature [14].…”
Section: < Table 3 >supporting
confidence: 87%
“…The NMR data for compound 6 were assigned for the rst time according to its 2D-NMR data. From the 1 H-NMR data in Table 3 data, compound 16 is consistent with 4-hydroxy-7,8-dimethoxy-furoquinoline, which has been previously reported in the literature [14].…”
Section: < Table 3 >supporting
confidence: 87%
“…These results indicated that the two -OCH 3 groups were at C-7 and C-8. The above nuclear magnetic resonance data showed compound 16 was consistent with 4-hydroxy-7, 8-demethy-furoquinoline, which has been previously reported in the literature[14], but no its 1D and 2D NMR data attribution was performed on it. Herein, its NMR data of compound 16 was also assigned.By the comparison of their NMR data with those described in the literature, twenty-six compoundswere identified as (+)-9′-O-transferuloyl-5, 5′-dimethoxylaricriresinol (1) [15], 8-(3′-oxobut-1′-en-1′yl)-5, 7-trimethoxy-coumarin (2) [16], 5, 7, 8-trimethoxy-coumarin (3) [14], 5-(3', 3'-dimethyl-2'butenyloxy)-7, 8-trimethoxy-coumarin (4), methyl 2-(5-methoxy-2-methyl-1H-indol-3-yl) acetate (5), ethyl 2′-(5, 6-dihydrochleletrythrine-6-yl) acetate (6), 6-acetonyldi-hydrochelerythrine (7) [18], 6βhydroxymethyldihydronitidine (8) [19], bocconoline (9) [20], zanthoxyline (10) [21], O-methylzanthoxyline (11) [21], rhoifoline B (12) [22], N-nornitidine (13) [23], nitidine (14) [24], chelerythrine (15) [25], 4-hydroxyl-7, 8-demethyfuroquinoline (16), dictamnine (17) [26], γ-fagarine (18) [27], skimmianine (19) [13], robustine (20) [26], R-(+)-platydesmine (21) [28], 4-O-methyl-1methyl-quinoline-2-one (22) [27], 4-methoxy-2-quinolone (23) [29], liriodenine (24) [30], aurantiamide acetate (25) [31], and 10-O-demethyl-12-O-methylarnottianamide (26) [32].…”
supporting
confidence: 87%
“…The NMR data of compound 6was assigned firstly according to its 2D-NMR. From the 1 H NMR data in Table 3, the coupling constant between the proton signals at δ demethy-furoquinoline, which has been previously reported in the literature [14].…”
Section: < Table 3 >mentioning
confidence: 76%
See 1 more Smart Citation
“…The IR spectrum showed the absorption bands for an aromatic ring (1516 and 1443 cm −1 ) and an ether (1151 and 1046 cm −1 ). The 1 H NMR data in Table 4 demethy-furoquinoline, which has been previously reported in the literature [14].…”
Section: Chemical Structure Of Compound 16mentioning
confidence: 63%